Description of the final-instar larva of Heliogomphus selysi Fraser (Odonata: Gomphidae) - Boonsoong, Boonsatien; Chainthong, Damrong (Zootaxa, 2014)
The final instar larva of Heliogomphus selysi Fraser, 1925, is described and illustrated for the first time based on specimens collected in Ratchaburi province, Thailand. Antennae, legs and paraprocts are similar morphologically to H. kelantanensis and H. scorpio but with a unique combination of dorsal hooks and lateral spines.